2022
DOI: 10.1007/s00216-022-03907-w
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive method to elucidate pyoverdines produced by fluorescent Pseudomonas spp. by UHPLC-HR-MS/MS

Abstract: Microbial secondary metabolites represent a rich source for drug discovery, plant protective agents, and biotechnologically relevant compounds. Among them are siderophores, iron-chelating molecules, that show a great influence on bacterial community assembly and the potential to control pathogen invasions. One of such a siderophore is pyoverdine that is produced by fluorescent Pseudomonas members and consists of different peptide chains specific to each bacterial species. The identification and structural eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…In this regard, Rehm and co-workers showed that searching for the ferribactin fragment ion turned out to be useful for the detection of several PVD variants from Pseudomonas spp., including unusual congeners bearing an isopyoverdine chromophore. Moreover, these authors developed a mass calculator and fragmentation predictor Excel tool for fast dereplication of PVDs, thus fostering discovery of novel derivatives by HR-MS based approaches [ 171 ].…”
Section: Analytical Methods For the Identification Of Pvdsmentioning
confidence: 99%
“…In this regard, Rehm and co-workers showed that searching for the ferribactin fragment ion turned out to be useful for the detection of several PVD variants from Pseudomonas spp., including unusual congeners bearing an isopyoverdine chromophore. Moreover, these authors developed a mass calculator and fragmentation predictor Excel tool for fast dereplication of PVDs, thus fostering discovery of novel derivatives by HR-MS based approaches [ 171 ].…”
Section: Analytical Methods For the Identification Of Pvdsmentioning
confidence: 99%
“…Furthermore, the pyoverdines of 13 Pseudomonas environmental isolates were investigated. They were sampled from soil and pond habitats on the campus of the University of Zurich Irchel (47.40° N, 8.54° E; Switzerland) (Butaite et al 2017 ) and their pyoverdine structures were elucidated in the work of Rehm et al ( 2022 ). A complete sample ID list is found in Table 1 stating the pyoverdine peptide chain sequences and their masses based on the pyoverdine derivative with a succinic acid side chain (Suc-Py) as recommended by Meyer et al ( 2008c ).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, an additional fast way to screen for specific pyoverdine signals during the same analysis run is desirable. This can be achieved by all ion fragmentation as conducted in the studies of Wei and Aristilde (2015) or Rehm et al (2022). Pyoverdines and related compounds give characteristic fragments containing the chromophore unit making a rapid identification of precursor candidates possible.…”
Section: Screening For Characteristic Pyoverdine Fragments: Applicati...mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3a shows that other secondary siderophores also occur in two forms: corrugatin vs. ornicorrugatin and quinolobactin vs. thioquinolobactin. Whether the chemical variation in these shows examples of peptide backbone variation found among P. aeruginosa strains (Schalk et al 2020) and among co-isolated natural strains (Rehm et al 2022). The blue box shows a list of side chain variants found among co-isolated natural strains (Rehm et al 2022) molecules also results in specificity, as shown for the pyochelin variants, remains to be tested.…”
Section: Iron Acquisition Through Siderophoresmentioning
confidence: 98%